Proceedings of the 54th Annual ACM SIGACT Symposium on Theory of Computing 2022
DOI: 10.1145/3519935.3520008
|View full text |Cite
|
Sign up to set email alerts
|

Counting small induced subgraphs with hereditary properties

Abstract: We study the computational complexity of the problem #IndSub(Φ) of counting 𝑘-vertex induced subgraphs of a graph 𝐺 that satisfy a graph property Φ. Our main result establishes an exhaustive and explicit classification for all hereditary properties, including tight conditional lower bounds under the Exponential Time Hypothesis (ETH): If a hereditary property Φ is true for all graphs, or if it is true only for finitely many graphs, then #IndSub(Φ) is solvable in polynomial time. Otherwise, #IndSub(Φ) is #W[1]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…This problem seems to be much harder. It is conjectured by Floderus, Kowaluk, Lingas, Lundell [9] that counting induced subgraphs for any k-vertex pattern graph is as hard as counting k-cliques for sufficiently large k. Several works have considered the parameterized complexity of counting subgraphs (See [5,4,17,10,7]) where the primary goal is to obtain a dichotomy of easy vs hard based on structural graph parameters. Some works have also considered restrictions on host graphs such as d-degeneracy [3].…”
Section: Related Workmentioning
confidence: 99%
“…This problem seems to be much harder. It is conjectured by Floderus, Kowaluk, Lingas, Lundell [9] that counting induced subgraphs for any k-vertex pattern graph is as hard as counting k-cliques for sufficiently large k. Several works have considered the parameterized complexity of counting subgraphs (See [5,4,17,10,7]) where the primary goal is to obtain a dichotomy of easy vs hard based on structural graph parameters. Some works have also considered restrictions on host graphs such as d-degeneracy [3].…”
Section: Related Workmentioning
confidence: 99%
“…Curticapean [22] further showed that counting matchings with k edges in a graph is also complete for #W [1]. These results led to several remarkable completeness results and new techniques (see, e.g., the works of Curticapean [23,24], Curticapean, Dell and Marx [25], Jerrum and Meeks [26], Brand and Roth [27], as well as recent advances [28,29]).…”
Section: Introductionmentioning
confidence: 99%
“…There is also a multi-coloured variant of the problem, MISWP(Φ), in which every vertex in G receives one of k colours, and we seek a k-vertex induced subgraph with property Φ and one vertex of each colour. See [43] for a survey of results on exact and approximate #ISWP(Φ) and #MISWP(Φ), and [27] for a more recent complexity classification of #ISWP(Φ) whenever Φ is a hereditary property. Observe that ISWP is a uniform witness problem, where the witnesses are the k-vertex subsets of V (G) which induce copies of graphs satisfying Φ, and Colourful-ISWP(Φ) is simply MISWP(Φ); hence Theorem 1.7 immediately implies that there is an FPTRAS for #MISWP(Φ) and #ISWP(Φ) whenever there is an FPT decision algorithm for MISWP(Φ), and moreover that the running times of these algorithms are the same up to a sub-polynomial factor in the instance size.…”
Section: Introductionmentioning
confidence: 99%